Boosting the Students’ English-Speaking Ability in Oral Descriptive Text - Maming, Khadijah; Sudarmanto; Afrida Aritonang (Universitas Sulawesi Barat, 2025)
his study describes the improvement of students' English speaking ability in oral descriptive text by using Tiktok videos. Tiktok videos can improve students' speaking skills because of the advantages of Tiktok as one of the learning media in vocabulary mastery. The tudents are interested in the existence of technology-based learning media that students are enthusiastic about learning when using cellphones. This study used a quantitative method of quasi experimental design. The population in this study were seventh grade students of MTsS DDI Takkalasi in the 2023/2024 school year. The overall population was 192 students and one class out of six classes was taken as a sample using the random sampling method. The instrument used to determine the results of improving student speaking using TikTok videos is using pretest and post test assessments. This type of research is classroom research with a quantitative approach. The results of data analysis stated that the use of tiktok videos can improve students' speaking skills, which is indicated by the results of the pretest in the experimental group (41.5) for a higher postest, namely (77.25) and from the results of the pretest control group (39.25) for a higher posttest, namely (76.75) at the t-test value (3.37) higher than the t-table value (2.042) at the 0.05 level. This indicates that H1 is accepted and H0 is rejected. This means that students who are taught using TikTok videos getting improvement on speaking skills which have better quality compared to students who are taught without using tiktok videos. The teachers also recognize the benefits of learning media on the use of technology is very helpful. The students also showed high enthusiasm and significant improvement in speaking skills after participating in learning activities using TikTok videos. This study concludes that TikTok can be an engaging and innovative tool for improving students' English-speaking skills, especially in the context of oral descriptive texts.